Impact of Climate on Diseases–A Case Study of North Bengal - Sharma, Sanjit Kumar Shil; Das, Vaskar; Sarkar, Bappa; Roy, Gobinda Chandra (American Journal of Biology and Natural Sciences, 2025)
Climate change is inducing uncertainty in decision making system through sudden onset of unprecedented temperature rise or intense precipitation within a very short duration, recurrent drought and flood and many such weather extremities. Northern eight districts of West Bengal forms North Bengal. It has a vibrant departure from rest of West Bengal in respect of its geographical position. The region is enriched with high mountain ranges, dense forests and a large number of rivers. The climatic condition of the region is quite different from the southern part of West Bengal. The soil of North Bengal is stony or sandy, somewhere dry or wet. In the spring and the autumn seasons, the weather conditions became unhealthy and gave rise to several diseases like fever, malaria, dysentery, chest and respiratory affections, rheumatism and some other diseases in a severe form. As temperature increases these diseases also speeds. The main objective of the paper is to find out how the change of climate effects on these diseases in this region. Both primary and secondary data are used to fulfil the objectives. Afforestation and pollution control can check the climate change as well as spreading these diseases. Human consciousness is also imperative for the prevention and protection from these diseases.